Hematological changes in pregnancy induced hypertension in their third trimester at Jhalawar Medical College, Jhalawar, India - Jhajharia, Neelam; Verma, Madhureema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pregnancy induced hypertension (PIH) is one of the most common and potential life-threatening complications of pregnancy. This study is aimed to investigate and correlate the hemoglobin, haematocrit, white blood cell count, lymphocytes and platelets in PIH patients in their third trimester. Method: Total 126 subjects were studied out of them 63 patients (case) and 63 healthy pregnant women (control) visiting the Obstetrics and Gynaecology department Jhalawar Medical College, Jhalawar were registered in the study and followed during their pregnancy. Two millilitre of blood sample was drawn aseptically using the 5ml syringe from the median ante cubital vein of all the cases and control participants into EDTA-anticoagulated tubes. Haematological parameter calculated by using Sysmex XN-9100™ Automated Haematology System. Results: The mean hemoglobin level of the case group (8.8206±2.53779) was significantly lower than that of the control group (9.7289±2.47033) (p<0.05). The mean platelet count of the case group (131.4937±62.05999) was significantly lower than that of the control group (324.9683±230.78764) (p<0.05). The mean lymphocytes level of case group (1.2510±0.56369) was significantly lower than that of the control group (1.9295±1.4150) (p<0.05). The mean WBC level of case group (36.3467±119.90635) was significantly high than control group (11.5260±4.83059) (p<0.05). The mean haematocrit level of case group (32.6851±7.29789) was significantly high than control group (30.0424±23.38116) (p<0.05). Conclusion: The mean hemoglobin, mean platelets and mean lymphocytes are lower in PIH patients. The mean WBC and haematocrit are higher in PIH patient.